An implicit function based approach to deterministic discontinuity modeling using trace data - Cepuritis, Peter (International Society for Rock Mechanics, 2012)
A methodology has been described that is capable of generating realistic 3-dimensional models of large-scale structures from mapped discontinuity trace data. The technique incorporates a search algorithm to hierarchically select traces based on a variety of criteria, such as orientation, genetic type, and surface characteristics. Implicit functions (based on radial basis functions) are utilized to interpolate surfaces between selected trace data to provide validated realistic surface geometries. The implicit function based modeling approach also provides the rock engineer with an important tool in rock mass modeling and excavation design. The deterministic discontinuity models can be output as meshed surfaces as direct input into 3-dimensional discontinuum and continuum numerical modeling.